ANALISIS PERBEDAAN PENDAPAT WARGANET INDONESIA DAN INTERNASIONAL TERKAIT AKSI BOIKOT PRODUK PENDUKUNG ISRAEL - Nugroho, Adityo Fajar; Avorizano, Arry (Jurnal Teknik Informatika dan Komputer, 2025)
The conflict between Israel and Palestine is now in the global spotlight. Because a number of company products openly donate money and goods to Israel. This has made people angry at Israel and the products that support it, thus calling for a boycott of products supporting Israel on social media. Therefore, researchers conducted sentiment analysis related to the boycott of products supporting Israel from social media X and YouTube using the Naïve Bayes algorithm with its three models, namely Multinomial, Bernoulli, and Gaussian on Indonesian and international citizens. As a result, the international dataset obtained a positive sentiment value of 79.79% with 600 data supporting the boycott, while the negative class obtained 20.21% with 152 data rejecting the boycott. Then the Indonesian dataset has a positive sentiment value of 51.78% with 1312 data supporting the boycott, while in the negative class 48.22% is obtained with 1222 data rejecting the boycott. So, in Indonesia and other countries, the majority of netizens call for a boycott of products supporting Israel through social media platforms X and YouTube. When evaluating the model, the BernoulliNB model obtained the highest accuracy value on both datasets. On the Indonesian dataset, BernoulliNB achieved an accuracy value of up to 89%. Then on the international dataset, it gets an accuracy value of 76%.